2022
DOI: 10.3390/su141811394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface-Attached Vertical Ribs on Wind Loads and Wind-Induced Responses of High-Rise Buildings

Abstract: Façade design tends to be diverse with increasing requirements for architectural functions in modern high-rise buildings, leading to various aerodynamic roughness conditions of the building surface. A typical practice is setting vertical ribs on the building façade. This study aims to clarify the effects of vertical ribs on the wind loads and wind-induced responses of high-rise buildings. The models with four vertical rib configurations were tested in the open and suburban exposures using the High-Frequency Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…During the entire life cycle, bridges can experience violent vibrations and sustain serious damages due to unsteady wind loads [3,4], compromising their structural safety and undermining their sustainability. At present, wind tunnel tests and computational fluid dynamics simulation are the prevailing methods used to determine the wind load on structures [5][6][7]. However, both methods have their limitations: wind tunnel tests can be costly, while CFD simulation is time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…During the entire life cycle, bridges can experience violent vibrations and sustain serious damages due to unsteady wind loads [3,4], compromising their structural safety and undermining their sustainability. At present, wind tunnel tests and computational fluid dynamics simulation are the prevailing methods used to determine the wind load on structures [5][6][7]. However, both methods have their limitations: wind tunnel tests can be costly, while CFD simulation is time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…They found that vertical ribs with a relative width of 4% can reduce mean force coefficients in the along-wind direction and attenuate cross-wind vibration by disrupting vortex shedding. Moreover, the ribs in the corner regions of the façade play a dominant role in disrupting vortex shedding [8].…”
Section: Introductionmentioning
confidence: 99%